2022
DOI: 10.1186/s12889-022-12701-3
|View full text |Cite
|
Sign up to set email alerts
|

Screen time and developmental health: results from an early childhood study in Canada

Abstract: Background Research has shown that longer hours of screen time are negatively associated with children’s healthy development. Whereas most research has focused on school-age children, less is known about this association in early childhood. To fill this gap, we examined the association between screen time and developmental health in preschool-aged children. Methods This study draws from a data linkage on children (N = 2983; Mean age = 5.2, SD = 0.3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 52 publications
2
24
0
1
Order By: Relevance
“…This has been demonstrated in previous studies, which found that passive screen time was associated with worse psychological, health and educational outcomes, whereas educational and interactive screen time were associated with higher education-related outcomes (Sanders et al, 2019). For instance, in the language domain, background television was found to be negatively associated with language skills, whereas educational programs were positively associated with language skills (Madigan et al, 2020) rodevelopment such as maternal stimulation, which were often overlooked in previous studies (Kerai et al, 2022;Zhao et al, 2022).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…This has been demonstrated in previous studies, which found that passive screen time was associated with worse psychological, health and educational outcomes, whereas educational and interactive screen time were associated with higher education-related outcomes (Sanders et al, 2019). For instance, in the language domain, background television was found to be negatively associated with language skills, whereas educational programs were positively associated with language skills (Madigan et al, 2020) rodevelopment such as maternal stimulation, which were often overlooked in previous studies (Kerai et al, 2022;Zhao et al, 2022).…”
Section: Discussionmentioning
confidence: 54%
“…Considering the mean screen time observed in 2015 cohort was 4.4 h, it would be expected that any changes in mean neurodevelopment scores due to screen time exposure would be very small. Overall, previous studies that have sought to investigate the potential impacts of total screen time on neurodevelopmental outcomes in children (Kerai et al, 2022; Madigan et al, 2019; Madigan et al, 2020; Radesky & Christakis, 2016; Ribner et al, 2020; Sanders et al, 2019; Stiglic & Viner, 2019; Supanitayanon et al, 2020; Zimmerman & Christakis, 2005) also showed weak evidence that the total amount of screen time negatively impacts cognitive development or is associated with poorer educational attainment (Stiglic & Viner, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 There is evidence suggesting the positive effects of ST, particularly with interactive ST, which can improve children’s reading development, 6 and foster learning abilities. 7 , 8 Evidence has also suggested excessive ST being linked to detrimental developmental health effects, 9 involving language, cognitive, social, and physical developmental setbacks. 10 Hence, ST and its impact on children require further exploration.…”
Section: Introductionmentioning
confidence: 99%